Perlindungan hukum bagi anak korban bencana alam - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstract Tsunami in Aceh causes not only social and humanity problems but also legal questions. One of legal implication is that the protection for children after disaster from other party who are not responsible. The protection for children from natural disaster refers to Act 23 of 2002 regarding Child protection which determines that child protection in natural disaster is in special enforcement, namely prosperity and security. Thus, this protection does not rely on the role of government only. Key words: child protection, natural disaster.